Preparation of nanostructured Bi-doped CdO thin films by sol-gel spin coating method - Dagdelen, F.; Serbetci, Z.; Gupta, R. K.; Yakuphanoğlu, Fahrettin (Elsevier, 2012)
The nanostructured Bi-doped CdO thin films were prepared using sol-gel spin coating method. The morphology and optical properties were investigated using atomic force microscopy (AFM) and UV visible spectroscopy. The AFM results indicate that the CdO films are formed from the nanoparticles and the grain size of the films is changed with bismuth doping level. The optical band gap values of undoped and Bi-doped CdO films were determined by optical absorption method. The band gap value of undoped CdO film was found to be 2.589 eV, on the other hand, the band gap values of Bi-doped CdO films were found to be in the range of 2.657-2.684 eV. The band gap value of the CdO films is increased with the content of Bi dopant. It is evaluated that the optical band gap and grain size of the CdO film could be controlled by Bi-doping. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Nanostructure; CdO film; Band gap; Sol-gel; Bismuth